Learning to emulate the wise : the genesis of Chinese philosophy as an academic discipline in twentieth-century China - Makeham, John, 1955- (Formation and development of academic disciplines in twentieth-century China series., 2012)
Learning to Emulate the Wise is the first book of a three-volume series that constructs a historically informed, multidisciplinary framework to examine how traditional Chinese knowledge systems and grammars of knowledge construction interacted with Western paradigms in the formation and development of modern academic disciplines in China. In the first book of its kind in English, John Makeham and several other noted sinologists and explore how the field of "Chinese philosophy" (Zhongguo zhexue), developed in the early decades of the twentieth century, exploring the field's growth and relationship with European, American, and Japanese scholarship and philosophy. The volume discusses an array of representative individuals and institutions, including Nishi Amane, Hu Shi, Zhang Taiyan, Liang Shuming, Xiong Shili, Tang Yongtong, Feng Youlan, Jin Yuelin, and a range of Marxist philosophers. The epilogue concludes by discussing the intellectual-historical significance of these figures and throws into relief how Zhongguo zhexue is understood today.